Теоретичне дослідження безступінчастої трансмісії автомобіля КрАЗ-63221-02 для ремонту нафтогазових свердловин - Кожушко, Андрій Павлович; Островерх, Олександр Олегович; Шевцов, Вадим Михайлович (НТУ "ХПІ", 2017)
Описано процес визначення динамічного фактора автомобіля для ремонту нафтогазових свердловин, який оснащено механічною та гідрооб’ємно-механічною трансмісією. Обґрунтовано вибір підходу для визначення передавального відношення в замкнутому контурі безступінчастої гідрооб’ємно-механічної трансмісії. Наведено результати порівняльного аналізу значень динамічного фактора при використанні на автомобілях для ремонту нафтогазових свердловин безступінчастої гідрообємно-механічної та механічної трансмісій.

In this paper we describe the process of determining the value of the dynamic factor for the vehicle KrAZ-63221-02 used to repair oil and gas wells,which is equipped with mechanical and hydrovolumetric-mechanical transmissions. Two approaches are proposed for determining the transmission number of the hydrovolumetric-mechanical transmission by constructing a system of equations describing the change in angular velocities of the hydrovolumetric-mechanical transmission elements and the formation of a transmission ratio in a closed circuit. The paper substantiates the choice of the approach to determine the transmission ratio in a closed circuit of a continuously variable hydrovolumetric-mechanical transmission. The values of the coefficient of efficiency for continuously variable hydrovolumetric-mechanical and mechanical transmissions are calculated. The results of the comparative analysis of the values of the dynamic factor for the vehicles used to repair oil and gas wells with continuously variable hydrovolumetricmechanical and mechanical transmissions are given.
Theoretical research of the continuously variable transmission of the vehicle KrAZ-63221-02 used to repair oil and gas wells
Keywords: гідрооб’ємно-механічна трансмісія; розгін; динамічний фактор; коефіцієнт корисної дії; acceleration; hydrovolumetric-mechanical transmission; dynamic factor; efficiency